2020
DOI: 10.1016/j.bbrep.2020.100788
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paracasei treatment modulates mRNA expression in macrophages

Abstract: Macrophage metabolic pathways show changes in response to various external stimuli. Especially, increased lipopolysaccharide, an important bacterial component and Toll-like receptor 4 agonist, can induce activity in various macrophage metabolic pathways, including energy production and biosynthesis, as well as high immune responses due to increase in differentiated M1 macrophages. In this study, we confirmed that Lactobacillus paracasei ( L. paracasei ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Probiotics have been shown to be useful in the prevention and treatment for various acute and chronic human diseases 10 . Probiotics can interact with the intestinal epithelium and modulate immune system of host 11 13 . Previous studies have been especially suggested that Lactobacillus spp .…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics have been shown to be useful in the prevention and treatment for various acute and chronic human diseases 10 . Probiotics can interact with the intestinal epithelium and modulate immune system of host 11 13 . Previous studies have been especially suggested that Lactobacillus spp .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, studies have reported that the expression of inflammatory cytokines in macrophages induced by L. paracasei is inherently weaker than other Lacticaseibacillus species [42,43]. L. paracasei may avoid hyper-polarization of M1 macrophages by downregulating the gene expression of glycolysis-related enzymes and membrane transporters [44]. As reported, TNF-α can downregulate PPAR-γ and C/EBP-α expression by activating NF-κB and MAPKs pathways, including ERK1/2, p38 MAPK, and JNK in adipocytes [7,45,46].…”
Section: Discussionmentioning
confidence: 97%